In vitro response of bone marrow mesenchymal stem cells (hBMSCs) on laser-induced periodic surface structures for hard tissue replacement: Comparison between tantalum and titanium. (December 2018) - Jorge-Mora, Alberto; Imaz, Naroa; Garcia-Lecina, Eva; O'Connor, Gerard M.; Gómez-Vaamonde, Rodolfo; Alonso-Pérez, Ana; Franco-Trepat, Eloi; García-Santiago, Carlota; Pino-Minguez, Jesús; Nieto, Daniel
Highlights: Laser induced periodic surfaces structure (LIPSS) were fabricated on tantalum and titanium surfaces. We have demonstrated in vitro that LIPSS are an efficient option to increase osteoblastic differentiation. LIPSS created increase statistically cell metabolism and similar inflammatory response to the material. Collagen is produced in more quantity and cells differentiate to osteoblast easily. Abstract: This study investigates the biological response of tantalum and titanium materials with Laser Induced Periodic Surface Structures (LIPSS) produced by a femtosecond laser at a wavelength of 1030 nm. Periodic surface nanostructures were formed by laser irradiation using a laser energy slightly above the damage threshold fluence for titanium and tantalum; pulses with a 500 fs pulse duration at a high repetition rate were applied to smooth polished tantalum and titanium surfaces with an original roughness value of 3.9 ± 0.2 nm and 3.1 ± 0.2 nm, respectively. We have demonstrated that LIPSS are an efficient option to increase osteoblastic differentiation of hBMSCs in vitro on titanium and tantalum surfaces. LIPSS modification created a statistically significant increase in cell metabolism; the best values were observed using an MTT assay. Similar improvements in inflammatory response to the material (IL-6 and TNF-alfa values) were also observed. Results also show that collagen is produced in greater quantities and cells differentiate to osteoblasts easily. These differences are seen from the beginning until the end point of the in-vitro trial over a 20 day duration.